PENGARUH POC LIMBAH BUDIDAYA IKAN LELE TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasilliensis Muell Arg.) - Irvan Maulana, Muhammad; Rosmalinda, Rosmalinda; Kurniawan, Tardi (Politeknik Negeri Ketapang, 2025)
Wastewater from catfish farming comes from leftover feed and feces that contain organic and inorganic materials. The wastewater from catfish farming has an organic C content of 0.06-0.62%; N 0.49-1.32%; F 0.06-0.35%; K 0.22-4.97% and pH 5.67-8.00. This study aims to determine the effect of liquid organic fertilizer (POC) from catfish farming waste on the growth of rubber seedlings and to identify the effective concentration of POC that influences the growth of rubber seedlings. The study used a completely randomized design (CRD) non-factorial consisting of 5 treatments and 5 replications for a total of 25 experimental units, with each unit containing 3 samples, resulting in a total of 75 samples. The treatments were L0: 0 mL L-1, L1: 150 mL L-1, L2: 250 mL L-1, L3: 350 mL L-1, L4: 450 mL L-1. The results showed that a concentration of 150 mL L-1 was able to enhance stem diameter, and a concentration of 250 mL L-1 was able to increase plant height. A concentration of 350 mL L-1 is able to increase the number of umbrellas and the wet weight of the seedlings, and the dry weight of rubber seedlings will increase when given POC with a concentration of 450 mL L-1.